Complex Production Processes and Wage Inequality - Tuomas Pekkarinen (Institute for the Study of Labor (IZA), 2004)
This paper studies how changes in the complexity of the firms' production technologies affect wage differences between and within tasks. In a production process where tasks are complementary, the employer may have an incentive to pay higher wages when using more complex technologies because the output of such processes is more effort-sensitive. We use linked employer-employee data from the Finnish metal industry. These data provide quantified information on the complexity of the tasks of individual workers. The average complexity of the tasks in the firm is used as a proxy for the complexity of the production process. We estimate the effect of the complexity of the production process on hourly wages at different levels of complexity of the worker's own tasks and at different parts of the conditional wage distribution within tasks. We find that the complexity of the firm's production process increases wages in all the tasks but that there are no significant differences in this effect across tasks. Finally, the effect of the complexity of the production process tends to be stronger at the high end of the conditional wage distribution within tasks.
Keywords: O33; J31; 330; technological complexity; wage inequality; Fertigungstechnik; Komplexitätsmanagement; Anforderungsprofil; Lohnstruktur; Metallindustrie; Schätzung; Finnland